Penerapan Model PJBL untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik pada Mata Pelajaran Sejarah Kelas X-J SMAN 7 Banjarmasin - Andi Yoga Sapoetra; Halimatus Sa’diah; Rochgiyanti Rochgiyanti (Journal on Education, 2023)
This research discusses the application of the project-based learning model in history learning in the X-J class at SMA Negeri 7 Banjarmasin with 40 students as well as its influence on students' historical liveliness of student learning and learning outcomes. The research method used is classroom action research conducted in two cycles. Data collection uses observation sheet instruments, interviews, written tests, field notes, and student worksheets. The results showed that the application of the project-based learning model in historical learning was able to improve the liveliness of student learning and student learning outcomes. This is indicated by the value obtained by students in each cycle. In the first cycle, the research success criteria set for the liveliness of student learning were 75,00 learners engaged actively in good physical, mental, and social activities in the process of learning, and learning outcomes for students were 75 on an assessment scale of 1–100. The results showed that the application of the model of project-based learning could increase the liveliness of learning, with an increase in cycle 1 of 67% to 92% and an average value between cycles of 80%. whereas in the first cycle, for the individual learning outcomes, the average value of learning completeness got an average value of 72,5%. In the second cycle, the average value of activity for learning completeness gets an average value of 95%, with a percentage of classical class completeness of 83,8%.